Inovasi Model Problem Based Learning (PBL) Menggunakan Microsoft Teams Berbantu Fishbone Diagram - widya eko nurazizah; Adetia Yeyen Purnamasari; Bambang Supriatno; Riandi Riandi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education has an important role in changing a person's life. However, in learning biology, difficulties often arise for students because of its complexity. The lack of innovation and the use of technology by teachers in biology lessons results in students being less trained in critical thinking and solving everyday problems. Low problem-solving ability can have an impact on the quality of human resources. Therefore, there is a need for innovative learning models to make learning more meaningful. This study aims to examine the innovation of Problem Based Learning (PBL) learning models using Microsoft Teams assisted by fishbone diagrams applied to environmental pollution material. Microsoft Teams was chosen because it can streamline learning time in class and fishbone diagrams can be useful to make it easier for students to formulate and solve problems. The research method used is a qualitative approach through literature study. The results of descriptive analysis from various reliable sources, such as journals and theses, provide an understanding of developing critical thinking skills and solving students' environmental pollution issues can be done through the PBL model innovation using Microsoft Teams assisted by fishbone diagrams. This research is expected to provide insight for educators in choosing the right learning model. Thus, this research contributes to the development of more effective education and prepares students to become quality human resources in the future.